Glucocorticoid-driven mitochondrial damage stimulates Tau pathology - Du, Fang; Yu, Qing; Swerdlow, Russell H; Waites, Clarissa L (Brain (London, England : 1878), 2023)
Abstract Prolonged exposure to glucocorticoids, the main stress hormones, damages the brain and is a risk factor for depression and Alzheimer's disease. Two major drivers of glucocorticoid-related neurotoxicity are mitochondrial dysfunction and Tau pathology; however, the molecular/cellular mechanisms precipitating these events, and their causal relationship, remain unclear. Using cultured murine hippocampal neurons and 4–5-month-old mice treated with the synthetic glucocorticoid dexamethasone, we investigate the mechanisms underlying glucocorticoid-induced mitochondrial damage and Tau pathology. We find that glucocorticoids stimulate opening of the mitochondrial permeability transition pore via transcriptional upregulation of its activating component, cyclophilin D. Inhibition of cyclophilin D is protective against glucocorticoid-induced mitochondrial damage as well as Tau phosphorylation and oligomerization in cultured neurons. We further identify the mitochondrially-targeted compound mito-apocynin as an inhibitor of glucocorticoid-induced permeability transition pore opening, and show that this compound protects against mitochondrial dysfunction, Tau pathology, synaptic loss, and behavioural deficits induced by glucocorticoids in vivo. Finally, we demonstrate that mito-apocynin and the glucocorticoid receptor antagonist mifepristone rescue Tau pathology in cytoplasmic hybrid cells, an ex vivo Alzheimer's disease model wherein endogenous mitochondria are replaced with mitochondria from Alzheimer's subjects. These findings show that mitochondrial permeability transition pore opening is a precipitating factor in glucocorticoid-induced mitochondrial dysfunction, and that this event stimulates Tau pathogenesis. Our data also link glucocorticoids to mitochondrial dysfunction and Tau pathology in the context of Alzheimer's disease and suggest that mitochondria are promising therapeutic targets for mitigating stress- and Tau-related brain damage. Du et al. identify a mechanism by which glucocorticoid stress hormones induce mitochondrial damage and tau pathology in mice, and show that therapeutic targeting of mitochondria may be a promising strategy for reducing stress-related neurotoxicity and cognitive impairment.